Fiber Cross Sectional Shape: A Persuadable Feature for Assessment of Acoustic Noise Control Property of Some Natural Fibers and Its Geometrical Modeling. Issue 17 (2nd December 2022) - Datta, Mallika; Nandi, Sayak; Nath, Devarun; Debnath, Sayandeep; Basu, Gautam
ABSTRACT: The effects of cross-sectional shape, fiber density, and porosity of flax, jute, okra, sisal, and wool fibrous assemblies on noise absorption coefficient have been investigated. The shape was described in terms of its shape factor and the depth of grooves on the fiber's surface. The number of lobes on the surface of the fiber, which is attributed to intrinsic variability, was utilized to construct the governing equation of shape factors. The shape factor tends to increase as the number of lobes increases. Shapes such as hexalobal (jute), pentalobal (flax), tetralobal (okra), trilobal (sisal), and circular (wool) affected noise control performance. The technique for order performance by similarity to ideal solution (TOPSIS) was used to rank the fibers for noise control performance based on five attributes namely, cross-sectional area, shape eccentricity, shape factor, bulk density, and porosity for validation. The technique confirmed the rank of the absorption performance of the fiber measured by transfer matrix method in impedance tube (ISO 10, 534–2). Okra rendered the best noise absorption for its multilobal shape, low density, and spatial arrangement. Wool having regular cross-sections resulted in much lower noise absorption performance.